Pengaruh Perencanaan Audit Kinerja, Pelatihan Berkelanjutan, dan Akuntabilitas terhadap Kualitas Hasil Audit Kinerja : (Studi Empiris pada Auditor Inspektorat Jenderal Kementrian Agama) - Handajani, Lili (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study examines the impact of planning performance audits, training sustainability, and accountability on the quality of performance audit results. Ensuring high-quality performance audits is essential for public sector institutions, particularly within the Ministry of Religious Affairs, to achieve transparency and good governance. Research focuses on how internal audit practices can be enhanced through specific organizational factors.Methods: 66 auditors out of 206 at the Inspectorate General of the Ministry of Religious Affairs were given a questionnaire, which was used to gather primary data for a quantitative study. Multiple linear regression techniques were employed to analyze the data and determine the impact of the three independent variables on the audit quality.Results: The findings show that planning performance audits, sustainable training, and accountability collectively have a significant positive effect on performance audit quality, with an R² value of 0.548. Among the three, accountability has the most substantial positive influence (coefficient = 0.782), while sustainable training shows a weak negative relationship (coefficient = -0.024)..Conclusion and suggestion: Improving planning and accountability can significantly enhance audit quality. However, training programs should be evaluated to ensure they are aligned with performance goals. It is recommended that organizations review the content and implementation of training to maximize its effectiveness in supporting audit outcomes.